(untitled) (LEARNing Landscapes, 2018)
This paper explores how teens used storytelling during a yearlong, extracurricular documentary film project. The project invited a group of 8-12 teens and university researchers to act as visual narrative inquirers in a local historic neighborhood. We explore the role of story, framing our project as a form of engaged pedagogy, and draw connections between storytelling and filming. We conclude that at the heart of the project is a shared dialogue. In this project, the scenario of filming enacted an encounter, and came to life through the stories the teens took in, and the stories they produced in response.